DETECTION OF BACKGROUND RADIATION USING OPTICALLY STIMULATED LUMINESCENCE (OSL) DOSIMETER IN PUBLIC SCHOOLS IN KUANTAN - SOHAIMI, NORHANNA; ROSLI, MOHAMAD AIZUDDIN FAIZ; JUNET, LAILA KALIDAH (International Journal of Allied Health Sciences, 2020)
Introduction: The objective of this paper is to measure the background radiation using optically stimulated luminescence (OSL) dosimeter in various public schools in Kuantan, Pahang and to compare the results with recommended value provided by regulatory bodies. Few researches relating to background radiation monitoring is done using OSL as the main dosimeter. Methods: Monitoring of background radiation level is obtained using NanoDot OSL dosimeters. Eight schools in Kuantan were randomly selected and chosen for the location of study. Post guard and assembly areas were chosen as location of OSLD placement. Data was collected within five cycles of data collection in which each cycle took about 48 hours of exposure. Data obtained is then analysed using Landauer microStar computer system. Amount of background radiation level is then compared with annual effective dose limit provided by regulatory bodies such as AELB, IAEA and ICRP. Results: The accumulated background radiation level in both post guard area and assembly area showed increasing pattern during period of data sampling. The highest annual dose in post guard area is found in SK Cenderawasih with the value of 1.3283 mSv per year while the lowest annual dose is found in SMK Alor Akar with 0.5459 mSv per year. The highest annual dose in assembly area is noted in SK Semambu with a value of 1.1980 mSv per year while the lowest reading is noted in SMK Tengku Panglima Perang Tengku Muhammad with 0.5100 mSv per year. Conclusions: Several factors can influence the reading of background radiation level which include geographical factors, building materials and surrounding environments. The background radiation levels in majority of schools do not exceed the recommended limit. The researchers suggested this study should be continued and involve all schools in Malaysia in order to monitor the background radiation level as well as to provide safe environment to our future generation.